The Effect Of Marketing Communications And Customer Experience Management Strategies On Customer Loyalty - Payak, Mantana; Phokha, Ampasri (Journal of Management Sciences Suratthani Rajabhat University, 2023)
Banking businesses must have broad communication and convenient access to information, keeping pace with technological changes. At the same time, information must be reliable, accurate, interesting, and can build trust and loyalty to the bank's products. Therefore, the researchers studied digital marketing and customer experience management strategies as important tools for building customer loyalty. The objectives were: 1) to study the level of opinions on digital marketing communication strategies of service users and the level of opinions on customer experience management strategies; 2) to study the level of opinions on loyalty of service users; 3) to study the relationship and influence of digital marketing communication strategies on user loyalty; and 4) to study the relationship and influence of effective customer experience management strategies on the loyalty of service users. The study consisted of 314 users of the Mymo application of the Government Savings Bank. The data collection tool was a questionnaire. The statistics used for data analysis were percentage, mean, standard deviation, multiple correlation analysis, and multiple regression analysis. The results showed that the overall opinion of the users of digital marketing communications, overall customer experience management strategies, and overall loyalty were high. Digital marketing communication had a statistically significant correlation with brand loyalty. The results of a regression analysis show that digital marketing communications affect brand loyalty. Customer experience management strategies affect brand loyalty in the same direction. Government Savings Bank can apply the research results to the organization's strategy to make applications well known and continually develop applications that can create a good experience for customers, resulting in continued loyalty to applications.